Relative human capital endowments: estimates for selected countries and implications for international capital flows - Erich Gundlach (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
Despite large rate of return differentials implied by persistent income differentials, relatively little capital flows to poor countries. The rate of return differentials are substantially reduced, however, if different human capital endowments are taken into account, as is shown for a limited sample of countries. Additionally accounting for human capital externalities based on independent empirical evidence turns around the predicted rate of return differentials in favor of the rich countries. Hence, the world economy may converge to a rather unequal distribution of incomes as long as human capital accumulation is neglected as the key variable limiting economic development.
Keywords: 330; Humankapital; Internationale Kapitalmobilität; Einkommensverteilung